Parental unemployment and child health - Eva Mörk; Anna Sjögren; Helena Svaleryd (Institute for Evaluation of Labour Market and Education Policy (IFAU), 2014)
We analyze to what extent health outcomes of Swedish children are worse among children whose parents become unemployed. To this end we combine Swedish hospitalization data for 1992-2007 for children 3-18 years of age with register data on parental unemployment. We find that children with unemployed parents are 17 percent more likely to be hospitalized than other children, but that most of the difference is driven by selection. A child fixed-effects approach suggests a small effect of parental unemployment on child health.
Keywords: I12; J13; 330; parental unemployment; child health; human capital